ANALISIS PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Yeni Nuraeni; Risyda Zulfa Azzahra; Istiqomah; Rahma Yunita; Revina Indah Puspita (Cahaya Ilmu Bangsa Institute, 2024)
This study aims to analyze the role of teachers in enhancing students' learning motivation in general. Learning motivation is one of the key factors that influences students' success in achieving optimal learning outcomes. Without sufficient motivation, students tend to face difficulties in absorbing lesson material, completing assignments, or taking exams. Therefore, it is essential for teachers to have effective strategies to stimulate and sustain students' learning motivation. Teachers play a very strategic role in building and maintaining students' learning motivation through various approaches and strategies tailored to the characteristics and needs of students. This research uses a descriptive qualitative method with a literature study approach. In this study, data is obtained from the analysis of journal articles, books, research reports, and other relevant sources discussing the role of teachers in enhancing students' learning motivation. The research findings indicate that the role of teachers includes several important aspects, including providing positive feedback, creating a supportive learning environment, adopting a personal approach to students, and using innovative teaching methods. Providing constructive positive feedback can boost students' self-confidence and motivate them to continue learning. In addition, creating a comfortable and supportive learning environment, both physically and emotionally, can make students feel more engaged in the learning process. A personal approach to students is also crucial for understanding their needs and challenges in learning, enabling teachers to provide more appropriate support. The use of innovative teaching methods, such as technology-based learning, collaborative learning, or task-based projects, can also enhance students' interest and motivation to learn.